PRDM12: New Opportunity in Pain Research. Issue 10 (October 2020) - Imhof, Sophie; Kokotović, Tomislav; Nagy, Vanja
Abstract : PRDM12 is a newly identified causative gene for a type of congenital insensitivity to pain disorder, which is characterized by the inability to perceive pain. Here, we discuss the (patho)physiology of PRDM12 function and the opportunities and challenges those data provide for novel therapeutic approaches in various pain disorders.